Biomassa de raízes em diferentes fitofisionomias de savana em Roraima - Santos, Jhonson Reginaldo Silva (2010)
The objective of this study was to estimate the root biomass in different savanna phytophysionomies of Roraima. The study was conducted between June 2009 to February 2010 in two areas where are established grids of the PPBio: Campo Experimental Água Boa (Embrapa-RR; 616 ha and 22 sampling plots) and the Campus Cauamé (UFRR; 498 ha and 12 sample plots). The stock of root biomass was obtained by a specific extractor in five soil layers: 0-10, 10-20, 20-30, 30-40 and 40-50 cm on four replicates in each sampling plots. Aboveground biomass was also obtained in order to establish root:shoot relations. The average of total stock without considering phytophysionomic type or soil class was 21.39 Mg.ha-1 in Água Boa and 15.35 Mg.ha-1 in Cauamé. The root diameter class more predominant was fine roots (Ø < 2 mm), with 99.7% and 98.33%, respectively. Considering the phytophisionomic type, it was obtained a better average in Grassland / campo limpo (Sg-cl) with 22.07 Mg ha-1 in the Água Boa, and Grassland / campo sujo (Sg-cs) with 16.56 Mg ha-1 in Cauamé. The mosaic Sg+Sp was the phitophisionomy which showed higher root:shoot; 1 : 3,13 (Água Boa) and 1 : 5,64 (Cauamé). The root biomass stock for soil classes showed higher level in GLEISOL (23.82 Mg ha-1; Água Boa) and RED LATOSOL (17.78 Mg ha-1; Cauamé). Considering the conjunction between phytophysionomic types and soil classes (Phytopedounit), GLEISOL / campo limpo was the higher average root biomass stock (23.82 Mg ha-1 in the Água Boa). For the Cauamé area, the highest average was the RED LATOSOL / campo sujo, with 17.78 Mg ha-1. The results suggest variation in root biomass conditioned to the both water available in the soil and phytophisionomic type. However, it’s necessary more studies to have a better understanding on root biomass distribution in the Roraima savanna.